Efficacy and Safety of Sirolimus for Blue Rubber Bleb Nevus Syndrome: A Prospective Study. (6th May 2021) - Zhou, Jiaolin; Zhao, Zichen; Sun, Tao; Liu, Wei; Yu, Zhongxun; Liu, Jingjuan; Yu, Yiqi; Ning, Shoubin; Zhang, Hongbing
Abstract : INTRODUCTION: Blue rubber bleb nevus syndrome (BRBNS) is a rare systemic venous malformation (VM) disease. The characteristic gastrointestinal (GI) bleeding from multiple VM lesions causes severe chronic anemia which renders most patients depend on lifelong blood transfusion and frequent endoscopic treatment with dismayed outcomes. Although recent case reports suggest that oral sirolimus (rapamycin) is effective, a comprehensive evaluation of its efficacy and safety is in need. METHODS: A prospective study was conducted for both pediatric and adult BRBNS patients with administration of sirolimus at the dose of 1.0 mg/m 2 to maintain a trough concentration of 3–10 ng/mL. Laboratory tests including complete blood count, biochemical profile, D-dimer, and whole-body magnetic resonance imaging were performed at baseline and 3, 6, and 12 months after treatment. Clinical indicators such as hemoglobin level, lesion size, and transfusion need were evaluated. Adverse effects were recorded regularly. RESULTS: A total of 11 patients (4 males and 7 females) with median age of 14 (range, 5–49) years were recruited. The average lesion size was reduced by 7.4% ( P < 0.001), 9.3% ( P < 0.001), and 13.0% ( P < 0.05) at 3, 6, and 12 months of sirolimus treatment, respectively. Hemoglobin increased significantly after 6- and 12-month treatment ( P = 0.006 and 0.019, respectively). Only 1 patient received blood transfusion once during the study. Patients' quality of life and coagulation function were improved. Grade 1–2 adverse effects including oral ulcers (81.8%), acne (27.3%), transient elevation of liver enzymes (18.2%), and hair loss (9.1%) were observed. DISCUSSION: Sirolimus reduces the size of VMs, alleviates GI bleeding, and eliminates transfusion dependence of patients with BRBNS. The drug-related adverse effects are mild and mostly self-limited. These findings support sirolimus as a first-line treatment for GI and cutaneous VMs of BRBNS (see Visual abstract, Supplementary Digital Content, http://links.lww.com/AJG/B819 ).